Bio‐derived nanomaterials for energy storage and conversion. Issue 9 (20th March 2021) - Powell, Matthew Dalton; LaCoste, Jed Donavan; Fetrow, Christopher James; Fei, Ling; Wei, Shuya
Abstract: This review covers recent progress and advancements in bio‐templating nanomaterials for use in energy applications. Viruses, bacteria, and fungus, as well as plant and animal biomasses such as woods, coffee grounds, and crab shells, can be used as the templates or carbon sources for metal‐ and carbon‐based nanomaterials. Here we provide an overview of each of these materials as a template, with emphasis on the synthesis methods and qualities of nanomaterials fabricated using these templates. Research in this field is understandably diverse, as such, we aim to further its development by providing a timely summary of current research. We anticipate that this field will continue to prove highly applicable to the salient and growing topics of renewable energy. Abstract : A review covering recent applications of bio‐templates to the fabrication of nanomaterials for use in energy applications. This review covers viral, bacterial, and fungal templates; as well as wood, coffee grounds, crab shell, and other plant and animal biomass. These applications are promising to research in energy storage and conversion.